Perbandingan Level Tepung Gamal (Gliricidia sepium) dan Tepung Lamtoro (Leucaena leucocephala) Yang Berbeda terhadap Parameter Kimia Wafer Sebagai Pakan Ruminansia Kecil - Kornelia Kefe; Oktovianus R. Nahak T. B.; Gerson F. Bira (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
The purpose of this study was to determine the chemical quality of wafers using gamal flour (Gliricidia sepium) and lamtoro flour (Leucaena leucocephala) with different levels as small ruminant feed. This research was carried out at the Faculty of Agriculture, University of Timor in May to June 2019. Making wafers was carried out at the Faculty of Agriculture, while the analysis of feed quality was carried out at the Feed Chemistry Laboratory of the Faculty of Animal Husbandry Undana Kupang. The variables measured in this study were crude protein content, crude fat content, crude fiber content, dry matter, organic matter and BETN. The materials used in this study were gamal flour, lamtoro flour, rice bran, corn flour, mineral mix, starch flour, water. The method used is a Completely Randomized Design with the following treatment: R1 = Gamal Flour 20% + Lamtoro Flour 60% + Rice Bran + Corn Corn 8% + Mineral mix 2%, R2 = Gamal Flour 40% + Lamtoro Flour 40% + Bran Rice 10% + Corn Flour 8% + Mineral mix 2%, R3 = Gamal Flour 60% + Lamtoro Flour 20% + Rice bran 10% + Corn Flour 8% + Mineral mix 2, R4 = 80% Gamal Flour + Lamtoro Flour 0% + Rice Bran 10% + Corn Flour 8% + Mineral mix 2%. The results showed that there was a significant effect (P <0.01) on the chemical quality (dry matter, organic matter, crude protein, crude fat, crude fiber and BETN) wafers for small ruminants made with comparison of different gamal flour and lamtoro flour . It was concluded that the comparison of the levels of gamal flour and lamtoro flour in making wafers for small ruminant animals had different impacts on the quality of the chemical produced, but in general a ratio of 40% gamal flour and 40% lamtoro flour (R2) had the highest effect on the parameters of Quality Parameters Dry Ingredients, Organic Ingredients, Crude Protein and Crude Fiber.